2014
DOI: 10.1186/1471-2334-14-150
|View full text |Cite
|
Sign up to set email alerts
|

Lower ribavirin biodisponibility in patients with HIV-HCV coinfection in comparison with HCV monoinfected patients

Abstract: BackgroundIn HIV infected patients, the impact of ribavirin (RBV) pharmacology on sustained virologic response (SVR) to hepatitis C virus (HCV) treatment has not been fully investigated. The objective of this study was to compare the early RBV plasma exposure between a population of HIV-HCV coinfected patients and an HCV monoinfected group.MethodsEarly RBV plasma exposure (expressed as Area Under the Curve (AUC) from 0 to 4 h) after a 600 mg first dose of RBV was measured in a population of HIV-HCV coinfected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…The steady‐state ribavirin plasma concentrations found in this study were in the same range as previously published in HIV/HCV co‐infected patients . However, these plasma concentrations remained lower than reported ribavirin plasma concentrations in mono‐infected patients . We showed that haemoglobin concentrations dropped inversely with the raise of ribavirin plasma concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…The steady‐state ribavirin plasma concentrations found in this study were in the same range as previously published in HIV/HCV co‐infected patients . However, these plasma concentrations remained lower than reported ribavirin plasma concentrations in mono‐infected patients . We showed that haemoglobin concentrations dropped inversely with the raise of ribavirin plasma concentrations.…”
Section: Discussionsupporting
confidence: 87%
“…4 We observed the lowest DCV concentrations in a subject (patient 6) who experienced virological failure. Also patients 1 and 3 had low levels of DCV at week 4, but they reached higher concentrations at week 8; their better outcome may be referred to these different drug kinetics or to the absence of 93H quasispecies or to the activity of the other two components of the therapy.…”
Section: Discussionmentioning
confidence: 91%
“…In a recently published study, RBV area under the curve (AUC 0-4h ) within the first hours after RBV intake was significantly lower in a small group of coinfected compared to monoinfected persons. The conclusion was that lower early bioavailability of RBV could be one of the reasons for lower SVR rates in coinfected patients [ 23 ]. Our results with similar RBV steady state concentrations in coinfected compared to monoinfected patients of other cohorts, do not support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%